Development of an AR-based flipbook as an innovative learning resource - Rahayu, Sri; Meirawan, Danny; Muktiarni, Muktiarni; Ghinaya, Zahra; Sabitri, Zenita; Ismail, Affero (Universitas Negeri Padang, 2025)
In the 21st century, globalization and digital transformation have significantly altered human life patterns. Digital technology has become central to nearly all aspects of life, including the education sector in Indonesia. Technological skills and readiness to meet the demands of the job market have become increasingly critical. Vocational education, such as vocational high schools, aims to equip students with the competencies necessary to compete in the global market. However, challenges in enhancing the quality and relevance of education remain a significant issue. In fact, according to Indonesia’s Central Statistics Agency (BPS), the unemployment rate for vocational high school graduates reached 9.6% in 2023, the highest among all education levels, underscoring the urgent need for innovative approaches in vocational learning. One proposed solution is the development of flipbook-based learning media integrated with Augmented Reality (AR) to enhance student engagement and skills in the digital era. This study employed ADDIE (Analyse, Design, Development, Implementation, Evaluation). The results indicate that the VOCAR-FLIP model is significantly effective in improving students' learning outcomes, particularly in terms of academic achievement and conceptual understanding. These findings are expected to contribute meaningfully to the advancement of more innovative and effective educational technologies for future learning.